Passive strain sensing for structural health monitoring using retroreflective sheeting materials - Power, Hannah M.; Shenton III, Harry W. (Measurement : journal of the International Measurement Confederation, 2023)
•Retroreflectivity of retroreflective sheeting material changes with induced strain.•Strain and retroreflectivity are linearly related for some materials.•Strain sensitivity is dependent on the material type.•Retroreflectivity degrades with cyclic loading.•This passive strain sensor is low cost, practical, and straightforward. Retroreflective sheeting materials (RRSM) are used for various applications in engineering, although primarily for traffic signs. ASTM standards for RRSM specify required minimum retroreflectivities (RR). In this study, tests are conducted that show retroreflectivity decreases when the material is subject to tension, opening the possibility for using RRSM as a passive strain sensor for structural health monitoring that is low cost, practical, and innovative. Ten RRSM types were loaded in tension to 4,000 microstrain while measuring retroreflectivity and strain of the material. Results show that certain RRSM demonstrate a reasonably linear relationship between RR and strain. Furthermore, others do not return to their baseline retroreflectivity but degrade with repeated loading. Four of the materials are identified as the most likely to perform well as passive strain sensors.